Behavioral Biases in Investment Decisions: Investigating the Role of Financial Literacy as a Moderator in Nepal - Rana, Bikash; Sharma, Haridatta (Devkota Journal of Interdisciplinary Studies, 2024)
This study provides critical insights into investor behavior and its association with various behavioral biases in the context of investment decisions in Nepal’s financial markets. Data was collected from 260 individual investors using a structured questionnaire, and hierarchical regression analysis was applied to test the hypotheses. The research identifies significant biases, including anchoring bias, overconfidence, and herding, that influence investment decisions. Additionally, the role of financial literacy as a moderating factor was examined, revealing its significant impact on reducing the effects of these biases. The findings highlight the unique investment patterns in Nepal’s emerging market, contrasting with established norms in developed financial markets. These results are valuable for policymakers, regulators, and stock market authorities in addressing investor behavior, enhancing financial education, and promoting informed decisions